1993
DOI: 10.1099/0022-1317-74-7-1327
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical cross-linking of influenza A polymerase to its virion RNA promoter defines a polymerase binding site at residues 9 to 12 of the promoter

Abstract: A previous study of the 12 nucleotide-long influenza A virion RNA promoter has shown that three nucleotides, residues 9 to 11, were crucial for transcription in vitro, although other nucleotides play a significant but less important role. A model for polymerase-promoter recognition was proposed, according to which there were two sites: a binding site at residues 9 to 11 and a regulatory site at or near the site of initiation at residue 1. By studying the effect of point mutations in the promoter on the binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 19 publications
7
73
1
Order By: Relevance
“…Subunit PB1 has the binding activity of substrate nucleoside 5 H -triphosphates (Asano & Ishihama 1997;Asano et al 1995) and template RNA (Fodor et al 1993;Li et al 1998) and is involved in RNA polymerization (Nakagawa et al 1995;Kobayashi et al 1996). Both PB2 and PA associate with PB1 , thereby forming the ternary complex of functional RNA polymerase (Honda et al 1990;Kobayashi et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Subunit PB1 has the binding activity of substrate nucleoside 5 H -triphosphates (Asano & Ishihama 1997;Asano et al 1995) and template RNA (Fodor et al 1993;Li et al 1998) and is involved in RNA polymerization (Nakagawa et al 1995;Kobayashi et al 1996). Both PB2 and PA associate with PB1 , thereby forming the ternary complex of functional RNA polymerase (Honda et al 1990;Kobayashi et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Three nucleotides near the 3Ј end of the (Ϫ)-strand RNA were found to be required for synthesis, although accurate initiation was not demonstrated. Subsequently, these nucleotides were shown to be directly contacted by the influenza RdRp (29). However, additional data demonstrated the need for sequences located at the 5Ј end of the influenza RNA which form a partially double-stranded structure recognized by the RdRp (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…The 5' arm of the postulated cRNA panhandle was investigated for polymerase binding using the photochemical cross-linking protocol used previously to investigate the vRNA panhandle (Fodor et al, 1993(Fodor et al, , 1994. Radiolabelled 14 nucleotide-long RNAs based on the Y-terminal sequence of cRNA, including transversion mutations at each position, were incubated with nuclease-treated RNP at 30 °C for 30min.…”
Section: Cross-linking To the C R N A 5' Aimmentioning
confidence: 99%
“…The ability of added 3' end sequences alone to promote transcription was also observed when polymerase prepared by micrococcal nuclease treatment of viral cores was used (Seong & Brownlee, 1992a, b). Similar polymerase preparations were used to identify specific binding sites in the conserved 3' terminus of vRNA (Fodor et al, 1993). Also using the nuclease-treated polymerase derived from influenza virus, it was found that added 3' templates carrying certain mutations, which reduced transcription drastically, could have that activity 'rescued' if an RNA corresponding to the 5' arm of the panhandle with mutations designed to restore base-pairing with the mutant 3' arm was added.…”
Section: Introductionmentioning
confidence: 99%